2007
DOI: 10.1007/s00477-007-0142-1
|View full text |Cite
|
Sign up to set email alerts
|

Climate and human health: synthesizing environmental complexity and uncertainty

Abstract: Broad relationships between weather and human health have long been recognized, and there is currently a large body of research examining the impacts of climate change on human health. Much of the literature in this area examines climate-health relationships at global or regional levels, incorporating mostly generalized responses of pathogens and vectors to broad changes in climate. Far less research has been done to understand the direct and indirect climate-mediated processes involved at finer scales. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 64 publications
(97 reference statements)
0
29
0
3
Order By: Relevance
“…The association between HFRS epidemics and rainfall is still a matter of debate. Some studies showed that heavy rainfall followed by increased grass seed production was associated with higher deer mouse (Peromyscus maniculatus) densities, which caused an outbreak of hantavirus pulmonary syndrome in the Four Corners region of the United States, 13,16,17 and a negative relationship between rainfall and HFRS has also been reported. 8 There is no clear explanation for such difference, which may reflect heterogeneity in local climate conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between HFRS epidemics and rainfall is still a matter of debate. Some studies showed that heavy rainfall followed by increased grass seed production was associated with higher deer mouse (Peromyscus maniculatus) densities, which caused an outbreak of hantavirus pulmonary syndrome in the Four Corners region of the United States, 13,16,17 and a negative relationship between rainfall and HFRS has also been reported. 8 There is no clear explanation for such difference, which may reflect heterogeneity in local climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8][9][10][11][12] For example, increased grass seed production followed by heavy precipitation, as a result of the El Niñ o Southern Oscillation (ENSO), was found to be associated with higher Peromyscus maniculatus rodent density in southwestern United States and provides reservoirs for Sin Nombre virus. 13,[15][16][17] However, this result was not duplicated in other areas in the United States.…”
Section: Introductionmentioning
confidence: 86%
“…In the general assessment model of sustainable development and LST change, the change of LST is regarded as an important criterion upon which the evaluation of environmental quality and social and economic development policy can be based (Janssen, 1998;Tamerius et. al., 2007;Keller, 2008;Dai et.…”
Section: * Corresponding Authormentioning
confidence: 99%
“…O município de Campo Grande, localizado no centro desse Estado, está próximo de cidades com indústrias pesadas nas áreas químicas, refinaria, aço, de geração de energia como também, tem forte influência dos altos índices de queimadas realizadas para limpeza da terra para renovação de pastagens, o que resultou, e resulta, na péssima qualidade do ar na área de estudo. Compostos precursores do ozônio (VOCs, monóxido de carbono (CO) e NOx) à superfície, que tendem a acompanhar as condições meteorológicas, tornam o seu nível difícil de controlar (Tamerius, Wise, Uejio, Mccoy & Comrie, 2007).…”
Section: Introductionunclassified